1991
DOI: 10.1111/j.1471-0528.1991.tb10361.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of the pregnant woman with spinal cord injuries

Abstract: Summary. This paper forms part of an ongoing prospective study of pregnancy and labour in women with spinal cord injuries and combines a prospective and retrospective analysis of 17 pregnancies in 15 women with spinal injuries. The management and outcome in those 17 pregnancies is reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…This series suggested that there was a risk of preterm labour, as five preterm babies, less than 2500 g, and another three less than 3000 g were born out of 33 pregnancies that proceeded past six months. A review by Pereira 6 in 2003 synthesised the more complete data available from the four more recent case series 7–10 (1986–1993) and found that preterm birth rates ranged from 6–13%, which is similar to the published rates of preterm labour in the USA (in 1998) of 11% before 37 weeks gestation. However, this issue remains uncertain, with the three series using differing definitions for ‘pre‐term’ and the series sizes ranging from only 13 to 49, including spinal cord injuries at all levels.…”
Section: Discussionmentioning
confidence: 76%
“…This series suggested that there was a risk of preterm labour, as five preterm babies, less than 2500 g, and another three less than 3000 g were born out of 33 pregnancies that proceeded past six months. A review by Pereira 6 in 2003 synthesised the more complete data available from the four more recent case series 7–10 (1986–1993) and found that preterm birth rates ranged from 6–13%, which is similar to the published rates of preterm labour in the USA (in 1998) of 11% before 37 weeks gestation. However, this issue remains uncertain, with the three series using differing definitions for ‘pre‐term’ and the series sizes ranging from only 13 to 49, including spinal cord injuries at all levels.…”
Section: Discussionmentioning
confidence: 76%
“…Talvez em nosso caso, devido a baixa intensidade do estímulo doloroso da punção peridural sem botão anestésico prévio, não houve uma elevação tão grande da pressão arterial que provocasse bradicardia reflexa. A anestesia peridural tem sido considerada por muitos como o método mais eficaz para a prevenção da hiperreflexia autonômica durante o trabalho de parto espontâneo ou induzido e a operação cesariana 1,2,5, 16,20,[24][25][26][27][28] . A grande dificuldade está em avaliar o nível do bloqueio sensitivo dessas gestantes com lesões medulares altas, pois se houver falha parcial ou total do bloqueio peridural, o risco de desencadeamento da hiperreflexia autonômica durante o parto é alto 24,29 .…”
Section: Discussionunclassified
“…In our case, due to low painful stimulation of the epidural puncture without previous local infiltration anesthesia, blood pressure increase was not high enough to induce reflex bradycardia. Epidural anesthesia has been considered by many as the most effective method to prevent autonomic hyperreflexia during spontaneous or induced labor and Cesarean section 1,2,5, 16,20,[24][25][26][27][28] . The difficulty resides in evaluating sensory block level of those patients with high medullary injuries because there is a high risk of triggering autonomic hyperreflexia during labor if there is total or partial epidural block failure 24,29 .…”
Section: Discussionmentioning
confidence: 99%
“…AD is a life-threatening complication of SCI and is found in 85% of patients with lesions at or above the level of T6. 26 It results from loss of supraspinal control of the greater splanchnic sympathetic outflow. Afferent stimuli below the level of the SCI can result in an uncontrolled sympathetic outflow below the level of the lesion, causing a rise in blood pressure, activating the vagus nerve via baroreceptors causing bradycardia and vasodilation above the level of injury.…”
Section: Autonomic Dysreflexiamentioning
confidence: 99%